Evaluating artisanal fishing of globally threatened sharks and rays in the Bay of Bengal, Bangladesh. - Alifa Bintha Haque; Alifa Bintha Haque; Rachel D Cavanagh; Nathalie Seddon (PLoS ONE, 2021)
Sharks and rays are at risk of extinction globally. This reflects low resilience to increasing fishing pressure, exacerbated by habitat loss, climate change, increasing value in a trade and inadequate information leading to limited conservation actions. Artisanal fisheries in the Bay of Bengal of Bangladesh contribute to the high levels of global fishing pressure on elasmobranchs. However, it is one of the most data-poor regions of the world, and the diversity, occurrence and conservation needs of elasmobranchs in this region have not been adequately assessed. This study evaluated elasmobranch diversity, species composition, catch and trade within the artisanal fisheries to address this critical knowledge gap. Findings show that elasmobranch diversity in Bangladesh has previously been underestimated. In this study, over 160000 individual elasmobranchs were recorded through landing site monitoring, comprising 88 species (30 sharks and 58 rays) within 20 families and 35 genera. Of these, 54 are globally threatened according to the IUCN Red List of Threatened Species, with ten species listed as Critically Endangered and 22 species listed as Endangered. Almost 98% juvenile catch (69-99% for different species) for large species sand a decline in numbers of large individuals were documented, indicating unsustainable fisheries. Several previously common species were rarely landed, indicating potential population declines. The catch pattern showed seasonality and, in some cases, gear specificity. Overall, Bangladesh was found to be a significant contributor to shark and ray catches and trade in the Bay of Bengal region. Effective monitoring was not observed at the landing sites or processing centres, despite 29 species of elasmobranchs being protected by law, many of which were frequently landed. On this basis, a series of recommendations were provided for improving the conservation status of the elasmobranchs in this region. These include the need for improved taxonomic research, enhanced monitoring of elasmobranch stocks, and the highest protection level for threatened taxa. Alongside political will, enhancing national capacity to manage and rebuild elasmobranch stocks, coordinated regional management measures are essential.